PS 06-03 PERFORMANCE OF DIFFERENT MEASURES OF OBESITY AMONG THOSE WITH HYPERTENSION IN INDIA. (September 2016) - V, Nikhil S; Ghosh, Shreeparna; Jarhyan, Prashant; Gummidi, Balaji; Sharma, Yogesh; Gupta, Ruby; Mallipeddi, Bhaskara Rao; Reddy, K Srinath; Tandon, Nikhil; Prabhakaran, Dorairaj; Mohan, Sailesh
Abstract : Objective: Obesity is an important modifiable risk factor for hypertension and cardiovascular disease. Body mass index (BMI) is widely used to estimate obesity but considered often as not the best measure, particularly in South Asians. We compared the prevalence of obesity among Indian hypertensives, using different obesity measures and the performance of these measures. Design and Method: We conducted a representative population based cross-sectional survey, as part of a large community intervention study entitled UDAY, among 12245 participants aged ≥ 30 years, residing in rural and urban areas of North (Sonipat, Haryana) and South (Visakhapatnam, Andhra Pradesh) India. Participants were selected using a multistage cluster random sampling technique. Data were obtained using an interviewer administered questionnaire and anthropometry. Blood pressure was measured and defined according to the standard guidelines and definitions. Body fat was estimated by bio-electrical impedance. BMI, waist circumference (WC), waist-hip ratio (WHR) and percent body fat (PBF) were used to estimate the prevalence of obesity. The cut offs chosen were based on international recommendations for estimating obesity among South Asians (BMI, WC, WHR) and Obesity Algorithm ®, by the Obesity Medicine Association (PBF). Results: The age-standardized prevalence of hypertension was 28.2% (95% CI: 27.4% - 28.9%) while the age-standardized prevalence of obesity among hypertensives, using different measures is summarized in the table. The area under the curve with BMI as reference for WC was the highest among the three measures. WC performed well compared to BMI, with a sensitivity of 94.2% (93.0% - 95.3%) and specificity of 65.4% (63.0% - 67.8%). WC identified 535 hypertensives more than BMI as obese. These participants were more likely to be older and women. Conclusions: BMI underestimates obesity among Indian hypertensives. Waist circumference, which is easily measurable, can be an alternative measure to identify obese among hypertensives in community settings. Figure. No caption available.